Potential supply of lactic acid as a diversification alternative of the sugar agro-industry in Veracruz, Mexico - Castillo-Martínez, Jorge; Hernández-Rosas, Francisco; Ríos-Corripio, María; Varela-Santos, Elizabeth; Lizardi-Jiménez, Manuel; Hernández-Martínez, Ricardo (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
In Mexico, sugarcane (Saccharum spp.) is one of the most notable agrifood crops, due to the economic importance it represents, sucrose and ethanol are systematically produced from it. However, a modernization scheme is currently required through productive diversification, valorizing and taking advantage of the generated co-products. In this scheme, the production of lactic acid is proposed, which generates added value and has potential demand in different industries such as food and pharmaceuticals. Therefore, the objective of this research was to evaluate factors that determine potential supply of lactic acid, if it were produced using bagasse and molasses generated in 18 sugar mills located in four sugarcane regions in Veracruz, Mexico. Statistical methods of panel data analysis were applied by estimating five econometric models, using the factors that can determine such supply. Analysis results indicated that the four sugarcane regions have lactic acid production potential, highlighting the Papaloapan-Gulf (2.6 million t) and Cordoba-Gulf (1.6 million t) regions. Factors that influenced or determined supply were: harvest duration, lactic acid import price, the number of co-products and by-products, the harvested area and the average of schooling level. In conclusion, the sugar agroindustry in Veracruz has the potential to diversify its production through the co-production of lactic acid in the context of a deficit trade balance.